THE SIGNIFICANCE OF FORMING PSYCHODIAGNOSTIC COMPETENCIES IN PRIMARY CLASS TEACHERS - Abdumavlonov M. A. (Web of Journals Publishing, 2024)
The article talks about the importance of forming psychodiagnostic competencies in primary school teachers.
Keywords: primary education, psychodiagnostics, competence, psychology, character, education.